The Effect of Giving Honey Lime Juice (Citrus Aurantifolia) to Nausea Vomiting in Pregnant Women with Emesis Gravidarum : (In Murung Pudak Puskesmas Tabalong Regency South Kalimantan) - Dewi Wulandari; Anik Purwati; Maria Veronika Widiatrilupi (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Pregnancy is a natural process that many women undergo, but it is often accompanied by discomfort during antenatal visits. One of the most common symptoms during pregnancy is nausea and vomiting, known as emesis gravidarum, which typically occurs in the first trimester. Various natural remedies, such as lime extract, are believed to alleviate these symptoms. Lime, rich in essential limonin, linalool, and flavonoids, offers benefits for pregnant women by potentially relieving nausea and vomiting. Additionally, honey, when consumed during pregnancy, can support overall health and immunity. This study aims to investigate the effect of honey-lime juice (Citrus aurantifolia) on nausea and vomiting in pregnant women with emesis gravidarum at Puskesmas Murung Pudak, Tabalong Regency, South Kalimantan. The research design used a pre-experimental approach with a one-group pre-test post-test method. The intervention was administered for four consecutive days, during which the frequency of nausea and vomiting was measured on the first and fourth days. A purposive sampling technique was applied to select 30 pregnant women as participants. Data were collected through observation using the PUQE (Pregnancy-Unique Quantification of Emesis and Nausea) scoring system. The analysis was conducted using the Paired T-Test, which resulted in a p-value of 0.000, indicating a significant effect with a confidence level of α = 0.05. Therefore, it can be concluded that there is a significant effect of giving honey-lime juice in reducing nausea and vomiting in pregnant women with emesis gravidarum. This finding suggests that honey-lime juice could be an effective natural remedy to alleviate pregnancy-related nausea and vomiting, offering a promising alternative for managing this common pregnancy symptom.